2015
DOI: 10.1007/s12035-015-9445-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Burden Triggers Neurodegeneration via Production and Release of TNF-α from Astrocytes in Minimal Hepatic Encephalopathy

Abstract: Dopamine (DA)-induced learning and memory impairment is well documented in minimal hepatic encephalopathy (MHE), but the contribution of DA to neurodegeneration and the involved underlying mechanisms are not fully understood. In this study, the effect of DA on neuronal apoptosis was initially detected. The results showed that MHE/DA (10 μg)-treated rats displayed neuronal apoptosis. However, we found that DA (10 μM) treatment did not induce evident apoptosis in primary cultured neurons (PCNs) but did produce T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Importantly, DA released by midbrain dopaminergic neurons in both the striatum and the substantia nigra (Cheramy et al, 1981 ) controls GABA release through activation of D1 receptors located at the somato-dendrites and terminals of striato-nigral medium spiny neurons (Acosta-García et al, 2009 ). In addition, we have reported that DA influenced astrocyte function (Ding et al, 2014b , c , 2016 ). Therefore, it is imperative to elucidate the underlying pathogenesis of MHE as well as the appropriate therapeutic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, DA released by midbrain dopaminergic neurons in both the striatum and the substantia nigra (Cheramy et al, 1981 ) controls GABA release through activation of D1 receptors located at the somato-dendrites and terminals of striato-nigral medium spiny neurons (Acosta-García et al, 2009 ). In addition, we have reported that DA influenced astrocyte function (Ding et al, 2014b , c , 2016 ). Therefore, it is imperative to elucidate the underlying pathogenesis of MHE as well as the appropriate therapeutic drug.…”
Section: Introductionmentioning
confidence: 99%
“…While the features of macroscopic parts and the correlations with processing conditions are well understood, less information is available about μ P. It was reported that the degree of crystallinity of the μ P and the fraction of oriented polymer layer were larger, and the average size of the crystallites was smaller for μ P compared with parts produced by conventional injection molding . For polypropylene, the crystallinity and molecular orientation was observed to vary with the shear stress induced during μ IM .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have con rmed that the pathogenesis of MHE was caused by the abnormal elevation of intracranial DA [3,4,5,6,7,8]. It has been demonstrated as a novel regulatory mechanism that DA -induced astrocytic TNF-α release triggers progressive neurodegeneration, which leads to learning and memory decline in MHE [9]. Tumor necrosis factor-α (TNFα) signaling has been shown to regulate neuroin ammation, and plays roles in modulation of microglial activation [10], control of glutamatergic transmission and regulation of synaptic strength [11] in the central nervous system (CNS) [12].…”
Section: Introductionmentioning
confidence: 95%